Rubinstein–Taybi Syndrome in a Filipino Infant with a Novel CREBBP Gene Pathogenic Variant - Yumul, Rhea Camille R.; Chiong, Mary Anne D. (Case Reports in Genetics, 2022)
Rubinstein–Taybi syndrome (RSTS) is a rare genetic disorder characterized by dysmorphic facial features, broad thumbs and halluces, intellectual disability, and postnatal growth retardation. This report presents a male infant with microcephaly and characteristic facial features, namely, low anterior hairline, hirsutism, thin upper lip and micrognathia, broad thumbs and first toes, cryptorchidism, recurrent pneumonia, developmental delay, and growth retardation. Genetic testing showed a novel pathogenic variant in the CREBBP gene which is consistent with the clinical diagnosis of RSTS.